Writing for life: materials might make a difference - Falkenbach, Luciana Idiarte Soares; Fontana, Niura Maria (Brazilian English Language Teaching Journal)
This paper aims at identifying in two English textbooks, High Up (2013) and Freeway (2010), suggested by the Programa Nacional do Livro Didático (PNLD), which activities have greater potential to promote writing abilities for communication. To achieve such objective, both books were analyzed and compared taking into consideration the conceptions of language, text genres, teaching sequence, and writing as a process in English as an additional language. The conclusion of this examination shows that there is a distance between the textbooks authors’ intention of dealing with written language, in an interactionist perspective, and the teaching material. Throughout the article, some suggestions were put forward in order to improve the sequences by adjusting them to the theoretical views of the books. The findings reveal that one of the books explored activities that consider aspects of genre, audience, text purpose, and writing as a process